Transcriptome Analysis of Al-Induced Genes in Buckwheat (Fagopyrum esculentum Moench) Root Apex: New Insight into Al Toxicity and Resistance Mechanisms in an Al Accumulating Species - Xu, Jia Meng; Fan, Wei; Jin, Jian Feng; Lou, He Qiang; Chen, Wei Wei; Yang, Jian Li; Zheng, Shao Jian (Frontiers in Plant Science, 2017)
Relying on Al-activated root oxalate secretion, and internal detoxification and accumulation of Al, buckwheat is highly Al resistant. However, the molecular mechanisms responsible for these processes are still poorly understood. It is well known that root apex is the critical region of Al toxicity that rapidly impairs a series of events, thus, resulting in inhibition of root elongation. Here, we carried out transcriptome analysis of the buckwheat root apex (0-1 cm) with regards to early response (first 6 hrs) to Al stress (20 µM), which is crucial for identification of both genes and processes involved in Al toxicity and tolerance mechanisms. We obtained 34,469 unigenes with 26,664 unigenes annotated in the NCBI database, and identified 589 up-regulated and 255 down-regulated differentially expressed genes (DEGs) under Al stress. Functional category analysis revealed that biological processes differ between up- and down-regulated genes, although ‘metabolic processes’ were the most affected category in both up- and down-regulated DEGs. Based on the data, it is proposed that Al stress affects a variety of biological processes that collectively contributes to the inhibition of root elongation. We identified 30 transporter genes and 27 transcription factor genes induced by Al. Gene homology analysis highlighted candidate genes encoding transporters associated with Al uptake, transport, detoxification, and accumulation. We also found that transcription factors play critical role in transcriptional regulation of Al resistance genes in buckwheat. In addition, gene duplication events are very common in the buckwheat genome, suggesting a possible role for gene duplication in the species’ high Al resistance. Taken together, the transcriptomic analysis of buckwheat root apex shed light on the processes that contribute to the inhibition of root elongation. Furthermore, the comprehensive analysis of both transporter genes and transcription factor genes not only deep our understanding on the responses of buckwheat roots to Al toxicity but provide a good start for functional characterization of genes critical for Al tolerance.